Johnson, L. K. (2007): Strategic intelligence; Intelligence and the quest for security, Westport, Conn, Praeger Security International. Cinco Volúmenes - Díaz Matey , Gustavo (UNISCI Discussion Papers, 2010)
Sin resumen